Environmental microbial diversity and water pollution characteristics resulted from 150 km coastline in Quanzhou Bay offshore area - Ding, Siqi; Chang, Jiamin; Zhang, Wenzhou; Ji, Shouping; Chi, Yulang (Frontiers in Microbiology, 2024)
As a typical transitional area between the land and sea, the offshore area is subjected to the triple synergistic pressure from the ocean, land, and atmosphere at the same time, and has obvious characteristics such as complex and diverse chemical, physical, and biological processes, coupled and changeable environmental factors, and sensitive and fragile ecological environment. With the deepening of the urbanization process, the offshore area has gradually become the final receptions of pollutants produced by industry, agriculture, and service industries, and plays a key role in the global environmental geochemical cycle of pollutants. In this study, the Quanzhou Bay offshore area was selected as the research object. Sediment and water samples were collected from 8 sampling points within about 150 kilometers of coastline in the Quanzhou Bay offshore area. 16s rDNA high-throughput sequencing method was used to investigate the variation rule of microbial diversity in the offshore area, and multi-parameter water quality analysis was carried out at the same time. The results showed that the distribution characteristics of microbial communities and water quality in the Quanzhou Bay offshore area showed significant differences in different latitudes and longitudes. This difference is closely related to the complexity of offshore area.This study can provide scientific support for protecting and improving the ecological environment of offshore areas.